Internal Hemipelvectomy for primary bone sarcomas using intraoperative patient specific instruments- the next step in limb salvage concept - Amit Benady; Yair Gortzak; Summer Sofer; Yuval Ran; Netta Rumack; Avital Elias; Ben Efrima; Eran Golden; Ortal Segal; Omri Merose; Amir Sternheim; Solomon Dadia (BMC Musculoskeletal Disorders, 2022)
Abstract Background During pelvic Sarcoma resections, Surgeons often struggle to obtain negative margins while minimizing collateral damage and maintaining limb function. These complications are usually due to the complex anatomy of the pelvis. Here we present an accurate 3D surgical approach, including pre-operative printing of models and intraoperative patient-specific instruments (PSIs) for optimizing pelvic sarcoma resections. Methods This single-center retrospective study (N = 11) presents surgical, functional, and oncological outcomes of patients (average age 14.6 +/− 7.6 years, 4 males) who underwent pelvic sarcoma resections using a 3D surgical approach between 2016 and 2021. All patients were followed up for at least 24 months (mean = 38.9 +/− 30.1 months). Results Our results show promising surgical, oncological, and functional outcomes. Using a 3D approach, 90.9% had negative margins, and 63.6% did not require reconstruction surgery. The average estimated blood loss was 895.45 ± 540.12 cc, and the average surgery time was 3:38 ± 0.05 hours. Our results revealed no long-term complications. Three patients suffered from short-term complications of superficial wound infections. At 24 month follow up 72.7% of patients displayed no evidence of disease. The average Musculoskeletal Tumor Society (MSTS) score at 12 months was 22.81. Conclusion 3D technology enables improved accuracy in tumor resections, allowing for less invasive procedures and tailored reconstruction surgeries, potentially leading to better outcomes in function and morbidity. We believe that this approach will enhance treatments and ease prognosis for patients diagnosed with pelvic sarcoma and will become the standard of care in the future.